2019
DOI: 10.1159/000496828
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Seroprevalence and Primary Infection at the University Hospital Luigi Vanvitelli of Naples from 2007 to 2017

Abstract: Epstein-Barr virus (EBV) is a common herpesvirus that may cause asymptomatic infection or various diseases, such as mononucleosis, lymphoproliferative disorders and several cancers. Our objective was to estimate the prevalence of EBV among patients hospitalized in “Luigi Vanvitelli” University Hospital in the last 10 years. Our results showed that EBV seroprevalence in our geographical area was 65%. Seroprevalence increased gradually with age with no significant difference between females (49.42%) and males (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
6
2
Order By: Relevance
“…A Minnesota study reported 31% EBV prevalence among children aged 1-5 years, and a Swedish birth cohort study reported 7% prevalence by age 1 and 18% prevalence by age 2 (32,57). The higher EBV seroprevalence we observed among women differs from the majority of studies, which find no such association, although it has occasionally been reported (31)(32)(33)(34)38,58,59,60).…”
Section: 3 2020contrasting
confidence: 80%
“…A Minnesota study reported 31% EBV prevalence among children aged 1-5 years, and a Swedish birth cohort study reported 7% prevalence by age 1 and 18% prevalence by age 2 (32,57). The higher EBV seroprevalence we observed among women differs from the majority of studies, which find no such association, although it has occasionally been reported (31)(32)(33)(34)38,58,59,60).…”
Section: 3 2020contrasting
confidence: 80%
“…No significant differences were observed between male and female patients in agreement with the P. Courtright and S. K. West study [ 20 ]. On the contrary, several studies described a high incidence of ocular infections among male or female patients [ 21 , 22 , 23 ]. These gender rate variations may be due to many social factors and lifestyle habits.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature, several studies have been conducted to evaluate the antimicrobial activity of eye drops, both in vitro and in vivo. Celenza et al examined the antifungal activity of ozone-based eye drops on different strains of Candida, finding a significant inhibition [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%